In which direction do the efforts proceed? the European Union’s attempts to develop a common ımmigration and asylum policy - Şirin Öner, Aslı (Marmara Üniversitesi Avrupa Birliği Enstitüsü, 2012)
In the period which began in the mid-1980s and continued until today, there has been an increase in the number of refugees, asylum-seekers and irregular migrants. The Central and Eastern Europeans, who had the opportunity to participate in the migration movements with the removal of the political barriers and the persons displaced as a result of bloody conflicts in the Balkans played an important role in the increase in the number of people migrating to the Western Europe. The increase in the migratory pressures since the 1990s paved the way for the Western European states to tighten measures about immigration. This situation brought about the discussions on “fortress Europe” because the European Union tried to decrease the number of migrants entering the Union countries. However, the measures do not seem to be effective since more and more people enter the Union countries in an illegal way. This fact lies at the centre of the EU’s wish to develop a common immigration and asylum policy. In this regard, the aim of this article is to elaborate on the attempts to develop a common immigration and asylum policy within the context of turning the EU territories into an “area of justice, freedom and security”
Keywords: Immigration, Asylum, “Fortress Europe”, “Area of Freedom, Security and Justice”